2011
DOI: 10.1299/jsdd.5.681
|View full text |Cite
|
Sign up to set email alerts
|

Active Control of Vibrations in a Rolling Process by Nonlinear Optimal Controller

Abstract: In this paper a method of suppressing vibrations in an industrial rolling process with varying rotational frequency is presented. The vibrations in a rolling process are problematic as they do not only cause structural fatigue on the machinery, but also deteriorate the quality of the end product. The traditional approach for this type of a problem would be to avoid the critical frequencies of the process by changing the rotation speed of the reel, thus decreasing the vibrations. However, in practice this is ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This method is proposed by the authors for the mitigation of multidimensional tonal output disturbances (Orivuori and Zenger, 2011a). The method shares some similarities with the FSCF and IDC methods, as it is essentially based on finding an optimal solution for the LQ problem related to a plant model containing the dynamics of the disturbance.…”
Section: Direct Optimal Feedback Compensationmentioning
confidence: 99%
See 2 more Smart Citations
“…This method is proposed by the authors for the mitigation of multidimensional tonal output disturbances (Orivuori and Zenger, 2011a). The method shares some similarities with the FSCF and IDC methods, as it is essentially based on finding an optimal solution for the LQ problem related to a plant model containing the dynamics of the disturbance.…”
Section: Direct Optimal Feedback Compensationmentioning
confidence: 99%
“…This is achieved by setting the design parameter in Equation ( 37) to a very small value, say " ¼ 10 À8 , corresponding to an addition of a very small damping factor to the disturbance signal. It can be readily shown that the addition of the damping has practically no impact on the resulting control signal, although it is a suboptimal solution from the theoretical point of view (Orivuori and Zenger, 2011a).…”
Section: Direct Optimal Feedback Compensationmentioning
confidence: 99%
See 1 more Smart Citation
“…An immediate solution to the problem involves the use of continuous gain scheduling, in which the controller coefficients are modified according to the current disturbance frequency. To this end the disturbance frequency (usually the rotating frequency) has to be measured of tracked (Orivuori & Zenger, 2010;. The state estimator can be written in the forṁ…”
Section: Nonlinear Controllermentioning
confidence: 99%